Gendered vulnerability : how women work harder to stay in office - Lazarus, Jeffrey; Steigerwalt, Amy, 1976- (Legislative politics & policy making., 2018)
Gendered Vulnerability examines the factors that make women politicians more electorally vulnerable than their male counterparts. For instance, female candidates get less and lower quality coverage from the media; they face more and better quality political opponents; and they receive less support from their political parties. Beyond these purely electoral factors, women face persistent gender biases throughout society, which makes it more difficult for them to succeed and can also lead them to doubt their abilities and qualifications. These factors combine to convince women that they must work harder to win elections--a phenomenon that Jeffrey Lazarus and Amy Steigerwalt term "gendered vulnerability." Since women feel constant pressure to make sure they can win reelection, they devote more of their time and energy to winning their constituents' favor. For example, women secure more federal spending for their districts and states than men do; women devote more time and energy to constituent services; women introduce more bills and resolutions; and women's policy positions are more responsive to what their voters want. Lazarus and Steigerwalt examine a dozen different facets of legislative behavior, and find that across them all, female embers simply do a better job of representing their constituents than male members."--